Efeitos do hormônio do crescimento sobre vias de sinalização intracelular na miopatia associada à insuficiência cardíaca de ratos - Lima, Aline Regina Ruiz [UNESP] (2014)
Although chronic heart failure is usually associated with skeletal muscle atrophy, physiopathological mechanisms involved in muscle mass loss are not completed established. Growth hormone (GH) has anabolic effects. However, its effects on skeletal muscle preservation during catabolic diseases are not well understood. GH stimulates IGF-1, which activates PI3K/Akt pathway to inhibit atrogin-1 and MuRF-1. GH can also modulate myogenic regulatory factors and myostatin and follistatin protein expression as well as satellite cells activation. In this study, we evaluated the effects of GH administration on trophicity and intracellular signaling pathways involved in the atrophy process in peripheral skeletal muscles of rats with aortic stenosis (AS)-induced heart failure. After heart failure detection, GH was administered for 14 days (AS-GH group). Results were compared with those from Sham and non-treatment AS groups. Transthoracic echocardiogram was performed before and after treatment. Trophicity was analyzed in soleus and white portion of gastrocnemius muscles. Protein expression was evaluated by Western blot and satellite cells activation by immunofluorescence. Statistical analyses: ANOVA and Tukey or Kruskal-Wallis and Student-Newman- Keuls. Before treatment, AS groups presented similar echocardiographic parameters. GH attenuated systolic dysfunction. Sectional fiber areas of gastrocnemius did not differ between groups; in soleus, they were lower in both AS groups than Sham. In gastrocnemius, MRF4 and atrogin-1 were higher in AS and AS-GH groups. GH treatment attenuated MyoD increase. Immunofluorescence showed that staining with anti-neural cell adhesion molecule (NCAM) and antineonatal myosin heavy chain isoform were statistically more intense in AS-GH than AS and Sham. In soleus, GH activated IGF-1 and PI3K proteins. NCAM immunofluorescence was increased in both AS groups. In conclusion, GH treatment attenuates left ...